Kesadaran Perpajakan, Pelayanan Fiskus, Dan Kepatuhan Wajib Pajak (Studi Padawajib Pajak Orang Pribadi Yang Melakukan Kegiatan Usaha Dan Pekerjaan Bebas) - Nurwati Nurwati (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2016)
Taxpayer compliance from year to year shows declining. This study purposes to analyze the factors that affect the individual taxpayer Compliance conducting business and free trade in the region of KPP Pratama Jakarta Pasar Rebo. This study using the questionnaire as data collection. Respondents in this study are the individual taxpayers conducting business activities and work freely. This study uses a Tax Awareness, Service tax authorities as the independent variable and the Taxpayer Compliance as the dependent variable. The data were analyzed using multiple regression analysis using SPSS 20 for Windows. The results showed that (1) Awareness has negative influence on the Taxation Taxpayer Compliance significantly, (2) positive effect on the tax authorities Service Taxpayer Compliance significantly.